Disillusionment VERSUS Motivation (Journal of Parents and Teachers, 2024)
The article highlights the importance of motivation and the benefits it brings to students. When motivation is present, it creates a reason to take action, which can stem from either negative or positive incentives. For this to happen, it is essential to consider personal needs and the types of incentives that will be provided to achieve happiness.
Keywords: motivation; incentives; empowerment; development